Kontribusi konsep diri dan dukungan orang tua terhadap perencanaan karier siswa - Adek Eka Putra; A Muri Yusuf (JRTI (Jurnal Riset Tindakan Indonesia), 2022)
Career planning is an effort made by individuals to prepare themselves to enter the career world. Career planning is influenced by various factors including Self Concept and parental support. This study aims to: (1) describe  Self Concept, parental support, and career planning, (2) test the contribution of  Self Concept to career planning, (3) test the contribution of parental support for career planning, (4) test the contribution Self Concept and support of parents together in career planning.This research uses a descriptive correlational quantitative method. The population in this study were students of the MAN 2 Kota Padang grade XI which amounted to 430 students. The sample amounted to 214 students who were selected using the proportional random sampling technique.The results of the study aimed to describe that: (1) the average student's  Self Concept is in the high category, parental support is in a very good category and student career planning is in a good category (2) Self Concept contributes to career planning 36,2%, (3) parental support contributes to career planning by 20,6%, (4) Self Concept and parental support together  contribute to career planning by 22,5%. The implications of this study can be used as inputs for direct counseling teacher / counselor to provide guidance and counseling services, especially in the specialization and individual planning.